Source identification in distributed parameter systems - Skliar, Mikhail; Ramirez, W. Fred (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we solve the problem of the pointwise source identification of the convection-diffusion transport processes. This is done by converting the identification problem into an optimization problem of finding a spatial location and the capacity of a point source which results in the best match of model-predicted measurements to actual observed measurements.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka